Multi‐glomerular projection of single olfactory receptor neurons is conserved among amphibians - Weiss, Lukas; Jungblut, Lucas D.; Pozzi, Andrea G.; Zielinski, Barbara S.; O'Connell, Lauren A.; Hassenklöver, Thomas; Manzini, Ivan (Journal of comparative neurology (1911), 2020)
Individual receptor neurons in the peripheral olfactory organ extend long axons into the olfactory bulb forming synapses with projection neurons in spherical neuropil regions, called glomeruli. Generally, odor map formation and odor processing in all vertebrates is based on the assumption that receptor neuron axons exclusively connect to a single glomerulus without any axonal branching. We comparatively tested this hypothesis in multiple fish and amphibian species (both sexes) by applying sparse cell electroporation to trace single olfactory receptor neuron axons. Sea lamprey (jawless fish) and zebrafish (bony fish) support the unbranched axon concept, with 94% of axons terminating in single glomeruli. Contrastingly, axonal projections of the axolotl (salamander) branch extensively before entering up to six distinct glomeruli. Receptor neuron axons labeled in frog species (Pipidae, Bufonidae, Hylidae, and Dendrobatidae) predominantly bifurcate before entering a glomerulus and 59 and 50% connect to multiple glomeruli in larval and postmetamorphotic animals, respectively. Independent of developmental stage, lifestyle, and adaptations to specific habitats, it seems to be a common feature of amphibian olfactory receptor neuron axons to frequently bifurcate and connect to multiple glomeruli. Our study challenges the unbranched axon concept as a universal vertebrate feature and it is conceivable that also later diverging vertebrates deviate from it. We propose that this unusual wiring logic evolved around the divergence of the terrestrial tetrapod lineage from its aquatic ancestors and could be the basis of an alternative way of odor processing. The formation of an odor map in the olfactory bulb of vertebrates is based on the general assumption that axons of individual olfactory receptor neurons do not branch and connect to single glomeruli. Here, we show that this general principle does not apply to the olfactory system of amphibians, which exhibits a multi‐glomerular wiring scheme and a putatively different odor coding strategy. Our data underline the need to acknowledge biological diversity to fully understand odor coding in vertebrates.